(untitled) (International journal of artificial intelligence, 2025)
This article explores the valuation of green service enterprises within the framework of Uzbekistan's sustainable economic transition. It examines various methodological approaches to assess the economic, environmental, and social impacts of green services, emphasizing their role in promoting sustainability. The paper discusses the challenges and opportunities faced by Uzbekistan in integrating green services into its economic landscape, highlighting the importance of effective policies that support sustainable development. By analyzing case studies and best practices, the article aims to provide insights into how green service enterprises can contribute to a more sustainable economy while addressing local and global environmental concerns. The findings offer valuable recommendations for policymakers, businesses, and stakeholders involved in fostering a green economy in Uzbekistan.